TiO2 Nanonetwork on Rough Ti Enhanced Osteogenesis In Vitro and In Vivo. (September 2021) - Yang, W.E.; Huang, H.H.
The objective in this study was to enhance osteogenic responses (in vitro and in vivo) to roughened titanium (Ti) dental implants through the formation of superhydrophilic TiO2 nanonetwork surface structure. Sandblasting and acid etching (SLA) was used to roughen the Ti surface. An electrochemical anodization process was then used to form a superhydrophilic TiO2 nanonetwork on the SLA Ti surfaces. The pore size of the nanonetwork structure ranged from a few nanometers to more than 100 nm, which is on the same scale as many biological species. Human bone marrow mesenchymal stem cells were used as an in vitro test model. The TiO2 nanonetwork structure was shown to have a significantly positive effect on hydrophilicity, protein adsorption, cell adhesion, cell migration, cell mineralization, and the gene and protein expression of osteogenic markers. The osseointegration of an anodized SLA screw-type Ti dental implant was investigated in vivo via implantation in the femur of New Zealand white rabbits for durations of 4 or 12 wk. The presence of a superhydrophilic surface TiO2 nanonetwork was shown to significantly enhance the bone-to-implant contact of the roughened SLA screw-type Ti dental implants. Overall, the proposed superhydrophilic TiO2 nanonetwork structure on the roughened SLA Ti surface proved highly effective in enhancing osteogenic responses in vitro and in vivo.